Leading for School Inclusion and Prevention? How School Leadership Teams Support Shy Students and Their Teachers. Issue 7 (10th November 2021) - Solberg, Stine; Edwards, Anne; Nyborg, Geir
ABSTRACT: School shyness may have immediate and long-term detrimental effects. Drawing on cultural-historical understandings of motivated actions and conceptual and material tools, the study examined how ten school leaders in three Norwegian elementary schools interpreted and responded to the demands on the school in their work with shy children. Data comprised individual interviews and concluding school-based group conversations with leaders. The schools were recognized as enabling teachers' responsive work with shy children in classrooms and presented a useful tension between central direction by school leaders and the professional discretion that enabled teachers' responsive pedagogies. The leadership teams' focus was school inclusion through adaptive pedagogies. This strong focus on inclusion emphasized classroom-based Tier 1 universal interventions. There were Tier 2 targeted interventions with shy children undertaken by social teachers, but they could seem ad-hoc by depending on teachers' capacity to identify the need for them. The implications for school leadership are discussed.